Pengaruh corporate governance, profitabilitas, likuiditas dan solvabilitas terhadap corporate social responsibility disclosure - SHELA OCTAVIANI; STEVEN YAP (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to test and analyze empirically the influence of return on assets, return on equity, return on sales, earning per share, basic earning power, and economic value added toward stock price. This study was also to compare result of the previous research within the research. Sample of this research is mining companies that listed in Indonesia Stock Exchange for period 2009-2013. The purposive sampling is used as sampling technique, where 12 companies met the criteria and were analyzed using descriptive statistics and panel data regressions with fixed effect model to test the hypothesis. The result of this research shows that return on assets, return on equity, return on sales, earning per share, basic earning power, and economic value added do not influence stock price